Submesoscale Coherent Vortices in the Gulf Stream. Issue 5 (11th March 2019) - Gula, Jonathan; Blacic, Tanya M.; Todd, Robert E.
Abstract: Seismic images and glider sections of the Gulf Stream front along the U.S. eastern seaboard capture deep, lens‐shaped submesoscale features. These features have radii of 5–20 km, thicknesses of 150–300 m, and are located at depths greater than 500 m. These are typical signatures of anticyclonic submesoscale coherent vortices. A submesoscale‐resolving realistic simulation, which reproduces submesoscale coherent vortices with the same characteristics, is used to analyze their generation mechanism. Submesoscale coherent vortices are primarily generated where the Gulf Stream meets the Charleston Bump, a deep topographic feature, due to the frictional effects and intense mixing in the wake of the topography. These submesoscale coherent vortices can transport waters from the Charleston Bump's thick bottom mixed layer over long distances and spread them within the subtropical gyre. Their net effect on heat and salt distribution remains to be quantified. Plain Language Summary: The interior of the ocean is populated by small‐scale coherent vortices, which redistribute water properties on the scale of basins. These structures are very difficult to observe. They have no surface signature and small dimensions, on the order of 1–50 km, such that they are missed by satellites and sampled only by chance. Furthermore, climate‐scale ocean models do not resolve these type of motions and do not take into account their impacts for the large‐scale transport and distribution of heat, nutrients, and other materials. Understanding and parameterizing these phenomena within models is critical for a better prediction of climate. Here we present new observations of submesoscale coherent vortices from seismic images and glider sections in the region of the Gulf Stream. We use a numerical model at very high resolution to reproduce vortices with the same characteristics and to analyze their generation mechanism. These vortices are generated where the Gulf Stream interacts with a deep topographic feature called the Charleston Bump due to frictional effects and intense mixing in the wake of the topography. These vortices transport waters from the Charleston Bump's thick bottom mixed layer and act to spread them all around the subtropical gyre. Key Points: Submesoscale lenses of well‐mixed water are observed in seismic reflection images and glider sections across the Gulf Stream A realistic numerical simulation is used to characterize these lenses as anticyclonic submesoscale coherent vortices Submesoscale coherent vortices are generated where the Gulf Stream interacts with the Charleston Bump